2018
DOI: 10.11604/pamj.2018.31.202.16573
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the adverse events following immunization surveillance system in Guruve District, Mashonaland Central 2017

Abstract: Introduction An adverse event following immunisation is any untoward medical occurrence which follows vaccination. Frequency of adverse events ranges from 13% to 34% and they should be reported regardless of severity. From the beginning of 2016 to mid-2017, Guruve district in Zimbabwe did not report any AEFIs. This suggests the surveillance system may be failing to detect adverse events. We therefore evaluated the AEFI surveillance system in Guruve district. Methods We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…The low sensitivity might also be due to HCWs' lack of knowledge as well as inadequate community sensitization. Consistent with ndings by Constantine et al 2018, who showed that inadequate community sensitization and staff training led to a low sensitivity of the AEFISS [17]. Hence there is a need for staff training to promote a high sense of vigilance [6].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The low sensitivity might also be due to HCWs' lack of knowledge as well as inadequate community sensitization. Consistent with ndings by Constantine et al 2018, who showed that inadequate community sensitization and staff training led to a low sensitivity of the AEFISS [17]. Hence there is a need for staff training to promote a high sense of vigilance [6].…”
Section: Discussionsupporting
confidence: 61%
“…Our study showed that the sensitivity of AEFISS in both districts was low. This was attributed to the passive nature of the system which relies on voluntary reporting [11,[16][17][18]. The low sensitivity might also be due to HCWs' lack of knowledge as well as inadequate community sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the system is heavily reliant on voluntary reporting by caregivers and most of these caregivers were not reporting to the facilities. This may be because caregivers were not educated enough to know that they have to report these events, as found in a study by Constantine et al [ 3 ]. However, Chimusoro et al, had contrary findings where though caregivers had good knowledge on the surveillance system, they still did not report [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The adverse event may be any unfavorable or unintended sign, abnormal laboratory finding, symptom or disease. AEFIs may range from mild reactions such as fever or rash to severe reactions such as convulsions, coma and even death [ 3 ]. Based on the outcome of the event, the World Health Organization (WHO) has classified AEFIs as Serious and Non-serious which is used for regulatory classification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation